Media Development of Flipbook Digital-Based Learning to Increase Fiqh Learning Motivation for Students of Al Mawaddah Warrahmah Kolaka Islamic Middle School - Rahmah, Nur Azizah; Zakariah, M. Askari; Akbar, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to develop a Flipbook-based learning medium for the Fiqh subject at SMP IT Al Mawaddah Warrahmah Kolaka and to examine its feasibility, validity, and effectiveness in enhancing students’ learning motivation. The research employed a Research and Development (R&D) approach with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and achievement tests. The research instruments were validated by two experts—one in media and one in content—to ensure the quality of the developed product.The findings indicate that the Flipbook learning medium was deemed highly valid by the experts, with an average score of 4.85 for the media aspect and 4.94 for the material aspect. These assessments encompassed visual design, student engagement, efficiency, content presentation, conceptual accuracy, and the alignment of test items with the learning material. The Flipbook was proven to effectively capture students’ attention, present the material in a structured and communicative manner, and provide an interactive learning experience. Furthermore, trial results demonstrated an improvement in students’ learning motivation, particularly in terms of interest and active engagement in understanding Fiqh concepts, especially regarding sujud syukur, sujud sahwi, and sujud tilawah. In conclusion, the Flipbook is a feasible and innovative learning medium that supports 21st-century education. This study recommends the broader use of Flipbook media in other subjects and suggests follow-up experimental research to comprehensively measure its impact on student learning outcomes.